Development of Dart Game Media for Indonesian Ethnic Cultural Diversity in Elementary Schools - Ginting, Andi Lopa; Hafa, M. Fauzi; Ariyanti, Lita; Niku, Elpipres (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2024)
Learning media innovation is crucial in the elementary school environment because teachers need concrete objects to facilitate the transfer of knowledge during elementary school. This research aims to determine the development of dart game media on the subject of ethnic and cultural diversity in Indonesia, the development process and the feasibility of dart game media. The research method used is development (Research and Development) borg n gall, modified by Sugiyono. The research subjects were fifth-grade elementary school students in the city of Batu. The data collection used is observation, questionnaires, learning results tests and documentation. The results of this research concluded that the dart game media was feasible and could be used in learning based on achievement indicators, with results of 80% where students experienced an increase from the results of the pretest and post-test comparison